Análise da área de vulnerabilidade e estabilidade de tensão em sistemas elétricos com a inserção de parques eólicos - MATOS, Kayt Nazaré do Vale (2005)
The present dissertation evaluates the voltage sag and stability of the real electrical system with the insertion of wind farms. The voltage sags studies serve of base for determination of the vulnerability areas of the electrical system, in which, in turn, the aspects are investigated regarding the voltage instability caused by the integration of wind systems with asynchronous generators. For that, the computational program ANAQUALI developed by CEPEL (Centro de Pesquisas de Energia El?trica) was used. In the study of the voltage dynamic behavior due to short circuit, in which the wind system is inserted in the conceptions of fixed speed and variable speed, a computational program developed in the MATLABTM software is used. The results of these simulations evidence that variable speed wind system provides a larger voltage stability edge to the electrical system, due to presence of the speed and voltage control. These studies commonly are not applied to the distributed generation system, and therefore, this dissertation also contributes in this aspect, and the results can serve of base for the planning of wind parks inserted in conventional electrical systems.